ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN DI SMA NEGERI 1 KECAMATAN PAYAKUMBUH, STUDI KASUS KEBUTUHAN JENIS MEDIA PEMBELAJARAN OLEH GURU BIOLOGI - Diana Zulyetty (FKIP UMSB, 2018)
The media used in the Biology Learning process must be in accordance with the needs of the teacher as a facilitator because the Biology teacher knows what media is in accordance with the objectives and material of the lesson to be taught. Therefore, information about what learning media teachers need to support the Biology learning process needs to be known, besides being a consideration for schools to provide effective facilities, it can also be used as a basis for teachers and researchers in developing Biology learning media. This research was conducted using a survey method for Biology teachers in class XI at SMAN 1 in Payakumbuh Subdistrict. Data on the needs of biology learning media are obtained through questionnaires. The results showed that the type of media needed by teachers to support the Biology learning process in class XI Semester I in each Competency Standard was multimedia media (97%), followed by media power point (96.13%) and video media (93.47 %). Keywords: media needs, needs analysis, learning media